SIKAP DAN PERMINTAAN KONSUMEN RUMAH TANGGA TERHADAP DAGING AYAM RAS SEGAR DAN DAGING AYAM RAS BEKU DI KOTA BANDAR LAMPUNG - Mutiara Fadhila Sari; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
Along with the development of science and technology, broilers are not only sold in fresh but also in frozen condition.  This study aims to determine consumers’ attitudes and the factors that influence their demand of fresh broilers and frozen broilers in Bandar Lampung City.  This research was conducted at three markets namely Pasir Gintung, Koga, Way Kandis, and in three supermarkets namely Chandra Tanjung Karang, Chandra Teluk Betung, and Transmart.  The number of consumer respondents was 60 people, recruited accidentally.  Research data were analyzed using multiatribute Fishbein and Seemingly Unrelated Regression.  Consumers’ attitude showed that the color and the scent of fresh broilers and frozen broilers got the highest scores.  The demand of fresh broilers was influenced by the price of fish, the price of cooking oil, the price of tempeh, and the number of household members.  The demand of frozen broilers was influenced by the price of fresh broilers, the price of frozen broilers, the price of cooking oil, the price of tempeh, household total income, and the number of household members.  Key words: attitudes, consumer, demand, fresh broilers, frozen broilers